Teaching Cognitive Behavior Therapy to Postgraduate Health Care Professionals in Times of COVID 19 – An Asynchronous Blended Learning Environment Proved to Be Non-inferior to In-Person Training - Soll, Daniel; Fuchs, Raphael; Mehl, Stephanie (Frontiers in Psychology, 2021)
Training of postgraduate health professionals on their way to becoming licensed therapists for Cognitive Behavior Therapy (CBT) came to a halt in Germany in March 2020 when social distancing regulations came into effect. Since the German healthcare system almost exclusively relies on this profession when it comes to the implementation of CBT and 80% of those therapists active in 2010 will have retired at the end of 2030, it is critical to assess whether online CBT training is as satisfactory as classroom on-site CBT training. An asynchronous, blended, inverted-classroom online learning environment for CBT training (CBT for psychosis) was developed as an emergency solution. It consisted of pre-recorded CBT video lectures, exercises to train interventions in online role-plays, and regular web conferences. Training was provided at five different training institutes in Germany (duration 8–16 h). Postgraduate health care professionals (psychiatrists and psychologists) (n = 43) who received the online CBT training filled out standard self-report evaluations that assessed satisfaction and didactic quality. These evaluations were compared to those evaluations of students (n = 142) who had received in-person CBT training with identical content offered by the same CBT trainer at the same training institutes before the COVID-19 crisis. Both groups were comparable with respect to interest in the subject and prior knowledge. We tested non-inferiority hypotheses using Wilcoxon-Mann-Whitney ROC-curve analyses with an equivalence margin corresponding to a small-to-medium effect size (d = 0.35). The online training evaluations were non-inferior concerning information content, conception of content, didactic presentation, assessment of the trainer as a suitable role-model, working atmosphere, own commitment, and practical relevance. In contrast, we could not exclude a small effect in favor of in-person training in professional benefit and room for active participation. Our results suggest that delivering substantial CBT knowledge online to postgraduate health-professionals is sufficient, and at most incurs minimal loss to the learning experience. These encouraging findings indicate that integrating online elements in CBT teaching is an acceptable option even beyond social distancing requirements.